2018
DOI: 10.3390/v10050248
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Clinical Characterization of Chikungunya Virus Infections in Southeast Mexico

Abstract: Chikungunya fever is an arthropod-borne infection caused by Chikungunya virus (CHIKV). Even though clinical features of Chikungunya fever in the Mexican population have been described before, there is no detailed information. The aim of this study was to perform a full description of the clinical features in confirmed Chikungunya-infected patients and describe the molecular epidemiology of CHIKV. We evaluated febrile patients who sought medical assistance in Tapachula, Chiapas, Mexico, from June through July 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 54 publications
6
16
0
Order By: Relevance
“…As noted above, our clinical staff was convinced that the AFI peak seen in October and November 2014 ( Figure 2) reflected a "recurrence" of CHIKV; in actuality, it built on a DENV1 case cluster, with some ZIKV mixed in at the end, and a still unidentified presumptive pathogen responsible for the majority of cases. Although we recognize the difficulties inherent in making clinical arboviral diagnoses, our data reinforce the frequency with which arthralgias are seen in CHIKV cases (with knees, wrists, and ankles most commonly affected, in keeping with findings in studies in other locales [9,30]).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As noted above, our clinical staff was convinced that the AFI peak seen in October and November 2014 ( Figure 2) reflected a "recurrence" of CHIKV; in actuality, it built on a DENV1 case cluster, with some ZIKV mixed in at the end, and a still unidentified presumptive pathogen responsible for the majority of cases. Although we recognize the difficulties inherent in making clinical arboviral diagnoses, our data reinforce the frequency with which arthralgias are seen in CHIKV cases (with knees, wrists, and ankles most commonly affected, in keeping with findings in studies in other locales [9,30]).…”
Section: Discussionsupporting
confidence: 83%
“…Moreira et al [6] have recently summarized results of studies on the epidemiology of acute febrile illness (AFI) in Latin America [6][7][8][9][10][11]. Although these studies have provided a basis for identifying the major pathogens responsible for febrile illness in the region, diagnostic criteria and approaches have differed widely, with no study having the ability to screen for previously unidentified pathogens; across all 17 studies evaluated by Moreira [6], the median number of pathogens tested per individual was 3.5.…”
mentioning
confidence: 99%
“…Important reasons for the drastic re-emergence of CHIKV is the expansion of the mosquito vector to urban areas with poor hygiene conditions, progressing climate change as well as the continuous increase in global transportation systems 7 . While other mosquito-borne arboviruses, such as dengue virus (DENV), only cause symptoms in a small fraction of infected individuals, CHIKV infection causes clinical manifestations in approximately 85% of infected individuals 8 . Acute chikungunya fever typically manifests as a rapid-onset illness characterized by fever, (poly) arthralgia, myalgia, maculopapular rashes, headaches and nausea 9 .…”
mentioning
confidence: 99%
“…Human exposure prevalence for these viruses can be as high as 80% in some regions [10,11]. VEEV and CHIKV have been found to circulate in the same Central and South American regions [12][13][14][15]. For example, VEEV has been thought to be endemic in southern Mexico for decades, with seroprevalence rates between 18-75%, whereas the seroprevalence of CHIKV in southern Mexico has been determined by some studies to be as high as 85% [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…VEEV and CHIKV have been found to circulate in the same Central and South American regions [12][13][14][15]. For example, VEEV has been thought to be endemic in southern Mexico for decades, with seroprevalence rates between 18-75%, whereas the seroprevalence of CHIKV in southern Mexico has been determined by some studies to be as high as 85% [13,14]. Additionally, recent studies have indicated that antigenic cross-reactivity, antibody-mediated enhancement, and antibody cross-neutralization of alphaviruses can have a significant impact on the course of infection [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%